Advancing Freud's dream: A dynamic-relational neurobiologically informed approach to psychotherapy. Issue 2 (3rd July 2017) - Kinley, Jacqueline L.; Reyno, Sandra M.
Abstract : In this paper we outline a hierarchical, phase-based model of psychotherapy to address a range of psychopathology. The proposed hierarchy of intervention is informed by emerging evidence on the modulation, integration, and homeostatic rebalancing of subcortical and cortical neural networks involved in emotion modulation, self-referential processing, and mentalization. To illustrate our Dynamic-Relational Model, we include a case description detailing the clinical presentation and treatment goals/approaches at each phase of the intervention, and sessional vignettes to illustrate specific techniques. We suggest this model of treatment has significant implications for understanding the pathogenesis of mental disorders, and may inform prevention efforts that could potentially reduce the prevalence or burden of mental illness.